Materials for games - An overview on creating materials for games materials for games - Souza, Davi Amancio; Mota, Rosilane Ribeiro (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2021.19633, 2021)
This paper presents an overview on some game texturing concepts and on how creating materials and its textures might be approached, by different means and for different purposes. Even though creating most materials can be done using more commonly talked about workflows in tutorials, specially useful for beginners, this approach is limiting on what can be achieved both artistically and technically. This paper intends on diffusing the existence of these concepts and how they might be kept in mind when creating game assets. The focus will be on high resolution, realistic materials. However, most of the presented points also apply for more stylized work just requiring some adaptation.